Preclinical pharmacokinetics, pharmacodynamics, and toxicity of novel small-molecule GPR119 agonists to treat type-2 diabetes and obesity - Patil, Mohan; Casari, Ilaria; Thapa, Dinesh; Warne, Leon N.; Dallerba, Elena; Massi, Massimiliano; Carlessi, Rodrigo; Falasca, Marco (Biomedicine & pharmacotherapy, 2024)
The escalating global prevalence of type-2 diabetes (T2D) and obesity necessitates the development of novel oral medications. Agonism at G-protein coupled receptor-119 (GPR119) has been recognized for modulation of metabolic homeostasis in T2D, obesity, and fatty liver disease. However, off-target effects have impeded the advancement of synthetic GPR119 agonist drug candidates. Non-systemic, gut-restricted GPR119 agonism is suggested as an alternative strategy that may locally stimulate intestinal enteroendocrine cells (EEC) for incretin secretion, without the need for systemic drug availability, consequently alleviating conventional class-related side effects. Herein, we report the preclinical acute safety, efficacy, and pharmacokinetics (PK) of novel GPR119 agonist compounds ps297 and ps318 that potentially target gut EEC for incretin secretion. In a proof-of-efficacy study, both compounds demonstrated glucagon-like peptide-1 (GLP-1) secretion capability during glucose and mixed-meal tolerance tests in healthy mice. Furthermore, co-administration of sitagliptin with investigational compounds in diabetic db/db mice resulted in synergism, with GLP-1 concentrations rising by three-fold. Both ps297 and ps318 exhibited low gut permeability assessed in the in-vitro Caco-2 cell model. A single oral dose PK study conducted on healthy mice demonstrated poor systemic bioavailability of both agents. PK measures (mean ± SD) for compound ps297 (Cmax 23 ± 19 ng/mL, Tmax range 0.5 – 1 h, AUC0–24 h 19.6 ± 21 h*ng/mL) and ps318 (Cmax 75 ± 22 ng/mL, Tmax range 0.25 – 0.5 h, AUC0–24 h 35 ± 23 h*ng/mL) suggest poor oral absorption. Additionally, examinations of drug excretion patterns in mice revealed that around 25 % (ps297) and 4 % (ps318) of the drugs were excreted through faeces as an unchanged form, while negligible drug concentrations (<0.005 %) were excreted in the urine. These acute PK/PD assessments suggest the gut is a primary site of action for both agents. Toxicity assessments conducted in the zebrafish and healthy mice models confirmed the safety and tolerability of both compounds. Future chronic in-vivo studies in relevant disease models will be essential to confirm the long-term safety and efficacy of these novel compounds. [Display omitted] •Novel synthetic O-LPI mimetic compounds, ps297 and ps318 acts as GPR119 agonist.•Showed low gut permeability in vitro and minimal systemic availability in vivo.•In GTT, both agents corrected glucose excursion and modulated GLP-1 secretion.•Suggesting gut-restricted incretin modulation.•Appeared safe and tolerable in mice and zebrafish model.